ANALISIS TERHADAP JUAL BELI TANAH BERSYARAT MENURUT FIQH MUAMALAH STUDI KASUS DI KECAMATAN DELIMA - AHMAD NIDAL (AL-ILMU, 2023)
Buying and selling is part of ta'awun (mutual help). For buyers to help sellers who need money (profit), while for sellers it also means helping buyers who are in need of goods. Therefore, buying and selling is a noble deed and the culprit gets the pleasure of Allah SWT. Along with the development of the times, there have been many fiqh problems in society which sometimes had never clearly occurred during the time of the Prophet or during the time of the Imams of the school of thought, but when it is related to the principles or basic rules they are actually the same, or even the society is not sufficient. As for what often occurs among the community, the problem of buying and selling conditional land is that those who own land may sell it but have the right to buy it back in Islamic teachings, it is permissible. From the problems mentioned above, the author is interested in conducting a study entitled Analysis of Conditional Sale and Purchase of Land According to Fiqh Muamalah Case Studies in Delima District. The type of research used is qualitative research, the research approach used is an empirical juridical approach. The analytical approach in this study is a qualitative approach, which is a way of analyzing research results that produce descriptive data. The practice of conditional sale and purchase of rice fields that occurs in Delima District, Pidie Regency is an agreement that occurs between two parties between the seller and the buyer, where the land can be bought over by the land owner when it is due in accordance with the agreement that has been agreed upon and Implementation of conditional land sale and purchase practices This is a ba'i al wafa', namely buying and selling that takes place on the condition that the goods being sold can be bought back by the seller if the agreed timeframe has arrived, then this sale and purchase is not allowed because it is not in accordance with the theory of buying and selling in Islamic law, especially if there is no time specified for redemption of the land. Keywords: Sale and Purchase, Conditional Land, Fiqh Muamalat.